Identify the main faults on Kithkeh dome (Bai Hassan structure) using remote sensing techniques - المفتي د. طورهان مظهر; قنبر عقيل وهبي (Journal of Petroleum Research and Studies, 2019)
The structure of Bai Hassan is one of the main oil structures of the North Oil Company and the Northern Region. This structure consists of two domes (Kithkeh and Dauod). The present study focused on the Kithkeh dome as it is visible on the surface and contains many faults. For the purpose of identifying the main faults, ERMAPPER V.7 was used with digital satellite data from Landsat7-ETM system. On this basis, the main faults (ten groups) were determined and the effect of some of them under the surface, especially the change in the levels of G.O.C level BH- 129 and BH-7.7.